Machiavelli a very short introduction - Skinner, Quentin 1940- (Oxford University Press, 2000)
Machiavelli taught that political leaders must be prepared to do evil that good may come of it. Because of this he has gained a sinister reputation. Focusing on 3 major works, Skinner distils from them an introduction to Machiavelli's doctrines of clarity
Originally published: 1981. - Includes bibliographical references and index
Keywords: Machiavelli, Niccolò / 1469-1527; Machiavelli, Niccolò -- 1469-1527; Political science / Italy; Politisches Denken; Einführung; Biografie